2017
DOI: 10.4269/ajtmh.16-0658
|View full text |Cite
|
Sign up to set email alerts
|

Dosage of Sulfadoxine–Pyrimethamine and Risk of Low Birth Weight in a Cohort of Zambian Pregnant Women in a Low Malaria Prevalence Region

Abstract: Abstract. In Lusaka, Zambia, where malaria prevalence is low, national guidelines continue to recommend that all pregnant women receive sulfadoxine-pyrimethamine (SP) for malaria prophylaxis monthly at every scheduled antenatal care visit after 16 weeks of gestation. Human immunodeficiency virus (HIV)-positive women should receive co-trimoxazole prophylaxis for HIV and not SP, but many still receive SP. We sought to determine whether increased dosage of SP is still associated with a reduced risk of low birth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
(38 reference statements)
2
13
0
Order By: Relevance
“…This is consistent with extensive reports on beneficial associations between the use of IPTp-SP and low birthweight still seen in areas where the efficacy of SP to clear parasitaemia has clearly decreased [11,12]. Besides its anti-malarial activity, IPTp-SP appears to confer benefit through yet undefined pathways [19,20,54]. Sulfadoxine is a broad-spectrum antibiotic that possibly exerts an inhibitory effect against non-malaria causes of LBW and preterm birth [55].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with extensive reports on beneficial associations between the use of IPTp-SP and low birthweight still seen in areas where the efficacy of SP to clear parasitaemia has clearly decreased [11,12]. Besides its anti-malarial activity, IPTp-SP appears to confer benefit through yet undefined pathways [19,20,54]. Sulfadoxine is a broad-spectrum antibiotic that possibly exerts an inhibitory effect against non-malaria causes of LBW and preterm birth [55].…”
Section: Discussionsupporting
confidence: 86%
“…IPTp-SP appears to protect against malaria as well as other non-malarial causes of LBW such as sexually transmitted and reproductive tract infections (STIs/ RTIs). SP may exert its protection through antibacterial or anti-inflammatory actions [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Although administration of antiretroviral therapy (ART) to pregnant women, compared with not treating mothers, is associated with improved birthweight,15 and is clearly to the benefit of both mothers and infants, concerns remain about the safety of ART in pregnancy. As in other studies,16,17 Stoner and others found an association between ART and increased risk for low birthweight and preterm delivery 8. The reasons for this remain unclear, but may include modulation of the normal immune shift from Th1 to Th2 that occurs during pregnancy, other alterations in inflammatory cytokines, or possibly an increased risk of hypertension with resultant placental insufficiency 16.…”
mentioning
confidence: 65%
“…This is supported by evidence from a Zambian study which reported that the bacterial and parasitic effects of SP signi cantly improved the birthweight of neonates born to women who took more doses of SP during pregnancy. The Sulphadoxine component of SP provides a broad spectrum of anti-parasitic and bacterial activities (46). Thus, constant exposure via monthly update of SP could reduce microbial density and immunological reactions leading to adverse birth outcomes such as LBW (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%